Map of the World on the mercator projection : exhibiting the American continent as its centre. - Mitchell, S. Augustus (Samuel Augustus), 1792-1868 (S. Augustus Mitchell, 1881)
Map shows major cities, political divisions, submarine cables locations, expeditionary routes, and a partial coastline for the "Antarctic Continent." Includes notes, and tables on verso: Comparative lengths of rivers of Europe--Comparative lengths of rivers of Asia and Africa--Comparative heights of the principal mountains of the Eastern Hemisphere [illustrated]. Relief shown by hachures. Scale not given.